Denmark : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper examines the household debt situation in Denmark and factors that have contributed to the high level of household debt in the country. Various factors seem to account for the size of household debt, including large pension assets, a highly developed mortgage market, the availability of flexible mortgage products such as deferred amortization loans, indirect subsidies through tax preferences for home ownership, and a regulated rental market that limits mobility. The paper highlights that high household debt could pose direct risks to financial stability if the number of mortgage loan defaults rises sharply in the face of adverse shocks.